The unity between moral values and social politics in the educational mindset of the Ly – Tran dynasties - Dung, Nguyen Phan Thi Thuy (Linguistics and Culture Review, 2023)
Starting from the attributes and requirements of the history and society of Viet Nam in the 11th to 13th century, which was to build an independent, united, and mighty nation of Dai Viet culture; the request for the unity power of the whole country to fight against the brutal invasion of Nguyen - Mong invaders; along with the inheritance, fusion, and development of the humanity of Confucius, Buddhism, and Taoism based on the spiritual humanity values of Viet Nam, the mindset in the Ly - Tran dynasties era was created and developed, in which the core was the unity between moral values and social politics. This article focuses on discussing the unity between moral values and social politics in the education mindset of The Ly - Tran dynasties era, which is manifested in the purpose and content of the examination system, the close-knit-to-people mindset and laws, and ideology among Dai Viet society at that time.